TARI ARAK IRIANG MANJALANG MAMAK DI KANAGARIAN MUARO PAITI KECAMATAN KAPUR IX KABUPATEN LIMA PULUH KOTA: BENTUK PENYAJIAN - Nela Eka Fitri; Idawati Syarif; Desfiarni Desfiarni (FBS Universitas Negeri Padang, 2012)
This throught for description the form of Tari Arak Iriang Manjalang Mamak in Muaro Paiti Village Kapur IX subdistrick Lima puluh kota regency. The matter to be formula is : 1.Origin the dance. 2. Elements dance. 3.Description dance. The kind through are kualitatif through,the make description metode Analisis. Result of through is shape diskes,Tari Arak Iriang Manjalang Mamak is the shopiere display because this dance the order formation dancer. To be definite by ordinal expert in the row line. In the ceremony tradition Arrach accompanymennt Manjalang Mamak In Muaro Paiti village . In the front is dubalang ranking second is Bundo kanduang with the umbrella man,third row are mother’s brother, the fourth is religious man and umbrella man. Keyword: Tari, Arak iriang, Manjalang, Mamak, Bentuk penyajian.